XC endurance training theory - Norwegian style - Part III - Seiler, S.; Skjaerli, B. (2002)
Presented are furthrt basic philosophies of the Norwegian training system (in cross country) with some explanation and comments. - In general, avoid "Middle of The Chart" intensities - Training structure in cross country skiing